Ideas of Crusade and Holy War in De Expugnatione Lyxbonensi (The Conquest of Lisbon) - Phillips, Jonathan (Studies in church history, 2000)
The Second Crusade (1145-9) was, for the most part, a failure. One of its few successes was the capture of the Muslim-held city of Lisbon by contingents of Anglo-Normans, Flemings, and northern Rhinelanders travelling via the Iberian peninsula en route to the Holy Land. At its full extent the Second Crusade consisted of campaigns in the Levant, the Baltic, and the east coast of Spain, as well as the Lisbon expedition. By far the largest forces went to the Holy Land but, following a calamitous crossing of Asia Minor, the combined armies of the kings of France and Germany, along with the troops of the Latin settlers, retreated from the walls of Damascus after only five days. Because the crusade to the Levant had been preached so successfully by Abbot Bernard of Clairvaux, this dismal outcome attracted bitter criticism from contemporaries. The defeat was ascribed to the treachery of (variously) the Greeks, the Templars, the count of Flanders, and the Latin settlers, or the incompetence of King Louis VII of France and the papal legates. Some commentators believed the crusade to have been the work of the devil. Bernard himself argued that it was the judgement of God that had caused the expedition to fail. Other writers blamed the participants’ motives, most relevantly here the contemporary historian, Henry, Archdeacon of Huntingdon. He wrote: In the same year [1148] the armies of the emperor of Germany and the French king, which marched out with great pride under illustrious commanders, came to nothing because God despised them…. Meanwhile, a naval force that was made up of ordinary, rather than powerful, men, and was not supported by any great leader, except Almighty God, prospered a great deal better because they set out in humility. Truly ‘God resists the proud, but gives grace to the humble’. For the armies of the French king and the emperor had been more splendid and larger than that which earlier had conquered Jerusalem, and yet were crushed by very much smaller forces and were destroyed like a spider’s web. But no host had been able to withstand the poor men of whom I spoke above, and the large forces who attacked them were reduced to weakness.